Topical anaesthesia in patients with post‐thyroidectomy haemorrhage using the "spray‐as‐you‐go" technique. Issue 2 (30th December 2014) - Gao, Youguang; Lin, Xianzhong; Zeng, Kai; Lin, Caizhu
Summary: Postoperative haematoma following thyroidectomy is an uncommon but potentially life‐threatening complication. In such cases, awake fibreoptic intubation may be an option. We report our experience of performing awake fibreoptic nasal intubation in two patients with post‐thyroidectomy haemorrhage. We have designed a novel topical anaesthesia catheter that can pass through the working channel of the fibreoptic bronchoscope in order to apply topical solution to the airway mucosa. Topical anaesthesia was applied to the airway using a "spray‐as‐you‐go" technique via this catheter.